MODELING OF LEPROSY CASES IN NORTH SULAWESI USING NEGATIVE BINOMIAL REGRESSION - Fatikha, Sintia Nova; damayanti, ina; Fadri, Firda (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Tadulako, 2025)
Leprosy is a chronic infectious disease that remains a public health concern in Indonesia, particularly in provinces where the disease is still endemic. North Sulawesi Province is among the regions with relatively high leprosy incidence, indicating the need for province-level analysis to better understand the factors associated with the occurrence of the disease. This study aims to identify the factors influencing the number of leprosy cases in North Sulawesi Province. The explanatory variables considered include the percentage of people living in poverty, the number of health workers, the percentage of toddlers immunized with BCG, the percentage of the population covered by health insurance, the percentage of households with access to clean drinking water, and the percentage of households with access to proper sanitation. The study uses secondary data obtained from official publications of the Central Statistics Agency (BPS) of North Sulawesi Province for the year 2023. Since the response variable is count data, Poisson regression was initially applied. However, due to the presence of overdispersion, Negative Binomial Regression was employed as an alternative modeling approach to obtain more reliable parameter estimates. The results indicate that the percentage of the population covered by health insurance has a statistically significant effect on the number of leprosy cases, with higher coverage associated with a reduction in reported cases. Other variables were found to have no significant effect at the chosen significance level. In conclusion, the findings highlight the importance of health insurance coverage in reducing leprosy incidence in North Sulawesi Province. The use of Negative Binomial Regression proves to be appropriate for modeling overdispersed leprosy case data and can support evidence-based policymaking in leprosy control programs.